Hubungan Pengetahuan Perawatan Kaki Diabetes Dengan Motivasi Keluarga Dalam Merawat Anggota Keluarga Penderita Diabetes Melitus - M Taukhid; Eva Nur Aini; Dinda Chynthia Agniera D (STIKES Karya Husada Kediri, 2018)
Diabetes mellitus is a group of heterogeneous disorders characterized by hyperglycemia or elevated levels of glucose in the blood. The purpose of this research is to know the correlation of knowledge of diabetic foot care with family motivation in caring for family member of diabetes mellitus in Buduran and Pesudukuh Village Working Area of ​​Puskesmas Bagor, Nganjuk Regency. The design used correlation with Spearman Rho approach. Data collection using a questionnaire of knowledge and motivational questionnaires in treating Diabetes sufferers. Population 32 people, sample 32 people, with total sampling technique and using Spearman Rho statistical test (α = 0,05). The result showed that most of respondent (56,3%) had good category diabetic foot care knowledge and almost all of respondents had motivation in caring for family member of Diabetes Mellitus suffering 78,1% category enough. Result of statistic test obtained p-value = 0.009 <a 0,05 that is H1 accepted, mean there is relation between knowledge with motivation care of family member patient of DM. Knowledge and motivation in caring for family member of DM patient is influenced by education, age, interest, experience, culture of environment, and information expected for family with diabetics have good knowledge and high motivation in order to decrease the complications that occur in patients due to DM, especially siabetic foot complications in order to avoid amputation actions that resulted in decreased quality of life of patients.